Epidemiologic study of oral and paraoral malignancies in one cancer referral center in Isfahan in a 5-year period - Atousa Aminzadeh; Ahmad Motaghi; Ebrahim Mohammadi (Isfahan University of Medical Sciences, 2013)
AbstractIntroduction: Prevalence of malignancies is different in different communities and different at different times and locations in a community. Epidemiological studies can help recognize high-risk groups. The aim of this study was to evaluate the frequency of oral and paraoral malignancies based on patient age and gender and the area involved and the type of malignancy in one cancer referral center in Isfahan in a 5-year period from 2005 to 2010.Materials and Methods: In this retrospective descriptive/analytical study, data of 236 oral and paraoral malignancies was collected in a 5-year period from 2005 to 2010, along with data on age, gender and the area involved. The malignancies were divided into epithelial, salivary, hematologic, soft tissue and hard tissue groups based on their origin. Data was analyzed descriptively using SPSS.Results: Oral cavity malignancies comprised 1.8% of all the malignancies of the period in question. Mean age of patients with oral cavity malignancies was 54 years (56.5 years in men and 52 in women). Male-to-female affliction ratio was 2.2. The majority of the lesions were epithelial in origin (72%), followed by salivary (15%), hematologic (5.5%), soft tissue (2.9%) and osseous lesions (2.9%). A total of 20% of lesions had occurred in the larynx, with 17% in the tongue. The most common malignancy was squamous cell carcinoma (SCC) with a prevalence rate of 90% of epithelial lesions.Conclusion: SCC was the most common malignancy, with the highest prevalence rate in 56.6-year-old males in the larynx and tongue. Key words: Epidemiology, Head and neck neoplasms, Oral neoplasms